Studi Populasi Kepiting (Scylla sp.) di Hutan Mangrove Kecamatan Nguling Kabupaten Pasuruan - Nurul Fitriyah Ika Putri; Hari Santoso; Saimul Laili (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2020)
Mangrove crabs play an important role in aquatic ecosystems on the decomposition of organic waste in every activity. This study aims was to analyze the population density of mangrove crabs (Scylla sp). The sampling method was carried out directly in the field using trap tools provided by purposive sampling. Arrest of 20 ‘bubu’ in three different stations, namely station 1 mangrove density is good, station 2 is medium density, and station 3 is bad density. The study obtained three types of mangrove crabs, in station 1 the percentage obtained by Scylla serrata male 11% and females 33% those were higher than stations 2 and 3 i.e. 0%. The percentage of male and female type of Scylla olivacea in station 3 was higher i.e. 100% compared to stations 2 and 3. For the Scylla paramamosain male type station 1 was higher i.e. 26%, but for the highest female species at station 2 obtain 41%. Abiotic measurements at each station include temperature, salinity, water pH, dissolve oxygen, and humidity. The density of mangroves greatly affects the growth of crabs, because the higher the density of mangroves, the more produced litter. Keywords: mangrove crabs (Scylla sp), mangrove forest ABSTRAK Kepiting bakau berperan penting pada ekosistem perairan pada penguraian sampah organik di setiap aktivitasnya. Penelitian ini bertujuan untuk menganalisis tingkat kepadatan populasi kepiting bakau (Scylla sp). Metode pengambilan sampel dilakukan langsung dilapangan dengan menggunakan alat-alat perangkap yang disediakan secara purposive sampling. Penangkapan menggunakan 20 bubu di 3 stasiun berbeda, yaitu stasiun 1 kerapatan mangrove baik, stasiun 2 kerapatan sedang, stasiun 3 kerapatan buruk. Penelitian analisis hutan mangrove menunjukkan bahwa diperoleh 3 jenis kepiting bakau, pada stasiun 1 persentase yang didapat jenis Scylla serrata jantan 11% dan betina 33% lebih tinggi dibandingkan stasiun 2 dan 3 yaitu 0%. Persentase jenis Scylla olivacea jantan dan betina di stasiun 3 lebih tinggi yaitu 100% dibandingkan stasiun 2 dan 3. Jenis Scylla paramamosain jantan di stasiun 1 lebih tinggi yakni 26%, namun untuk spesies betina tertinggi di stasiun 2 sebesar 41%. Pengukuran abiotic di setiap stasiun meliputi, suhu, salinitas, pH air, DO, dan kelembapan. Semakin tinggi kerapatan mangrove, maka populasi kepiting yang ditemukan semakin besar. Kata kunci: kepiting bakau, hutan mangrove